2021
DOI: 10.1063/5.0034575
|View full text |Cite
|
Sign up to set email alerts
|

The impact of magnetic fields on momentum transport and saturation of shear-flow instability by stable modes

Abstract: The Kelvin–Helmholtz (KH) instability of a shear layer with an initially uniform magnetic field in the direction of flow is studied in the framework of 2D incompressible magnetohydrodynamics with finite resistivity and viscosity using direct numerical simulations. The shear layer evolves freely, with no external forcing, and thus broadens in time as turbulent stresses transport momentum across it. As with hydrodynamic KH, the instability here features a conjugate stable mode for every unstable mode in the abse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…The process that counteracts the small scale generation of magnetic energy, which is quantified in this Letter, can be traced to the nonlinear excitation of large-scale stable linear eigenmodes [12]. The dispersion relation that is associated with the shear-flow instability present in this study has a stable (damped) root which acts to return energy and momentum to the mean profile, and which is excited to a high level by the nonlinearity [13,14]. The nonlinear excitation of stable modes and their effect on turbulence levels and transport has been studied previously, particularly in the context of fusion-relevant gyroradius-scale turbulence [12,[15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…The process that counteracts the small scale generation of magnetic energy, which is quantified in this Letter, can be traced to the nonlinear excitation of large-scale stable linear eigenmodes [12]. The dispersion relation that is associated with the shear-flow instability present in this study has a stable (damped) root which acts to return energy and momentum to the mean profile, and which is excited to a high level by the nonlinearity [13,14]. The nonlinear excitation of stable modes and their effect on turbulence levels and transport has been studied previously, particularly in the context of fusion-relevant gyroradius-scale turbulence [12,[15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 72%
“…The nonlinear excitation of stable modes and their effect on turbulence levels and transport has been studied previously, particularly in the context of fusion-relevant gyroradius-scale turbulence [12,[15][16][17][18][19][20][21][22][23]. Recent studies have also shown that stable modes are excited in macro-scopic shear flow driven turbulence and transiently affect momentum transport [13,14]. However, critical features of counteracting straining motion of the stable modes, essential for large-scale sequestering of magnetic energy, have only come to light in the study described here.…”
mentioning
confidence: 99%
See 3 more Smart Citations